Direct oxidation of Si1-xGex layers using Vacuum-Ultra-Violet light radiation in oxygen - Chen, LP; Chan, YC; Chang, SJ; Huang, GW; Chang, CY (My University, 1998)
Oxidation of Si1-xGex films has been carried out by direct photo chemical Vapor deposition (direct photo-CVD) directly with activated O-2 induced by Vacuum-Ultra-Violet (VUV) light radiation, The Auger electron spectroscopy profiles show that no Ge-pileup layer at the oxide/Si1-xGex interface is observed after VUV-induced Si1-xGex oxidation process. The X-ray photoelectron spectroscopy analysis of the samples reveals that Si and Ge are oxidized simultaneously in oxidation process and a mixed oxide layer consisting both SiO2 and GeO2 is formed, This might be the reason that Cc pileup effect is eliminated in this study.
Keywords: SiGe; photo-CVD; VUV; Auger profile; X-ray photoelectron spectroscopy